Pemanfaatan Artificial Intelligence (AI) sebagai Media Pembelajaran pada Mata Pelajaran Desain Grafis di SMK YBPK Pare - Putra, Kristiono Widjaja; Syaikhu, Ahmad (SM Institute, 2025)
The utilization of Artificial Intelligence (AI) technology in education continues to advance rapidly, offering innovative solutions to enhance the effectiveness of learning processes. One of AI’s key advantages lies in its ability to personalize learning by adjusting content and teaching approaches to align with each student's needs, abilities, and learning styles. AI also contributes by automating routine tasks, providing real-time feedback, and offering precise design suggestions, allowing students to concentrate more on conceptual and artistic development in Graphic Design learning (Das & Rani, 2024). This study aims to describe the use and potential of AI as a learning medium in the subject of Graphic Design at Vocational High Schools (SMK), particularly in urban areas with adequate digital infrastructure. This research employs a qualitative approach through literature review and descriptive analysis of relevant academic sources and recent publications. The study focuses on the integration of AI through adaptive learning systems and intelligent tutoring systems (ITS), which dynamically present content, feedback, and learning recommendations in a personalized manner. The findings indicate that AI-based learning in Graphic Design enhances student engagement, accelerates conceptual understanding, and provides a more interactive and responsive learning experience. However, the implementation of this technology also faces challenges, especially regarding teacher readiness, the development of appropriate instructional design, and issues related to ethics and student data privacy. The successful integration of AI into Graphic Design education in vocational schools requires strong collaboration among educators, technology developers, and school management to create a contextual and sustainable learning system. In addition, continuous teacher training and the strengthening of technology-based education policies are essential factors to consider. The results of this study are expected to serve as a foundational reference for the development of AI-based instructional innovations that are not only technically effective but also pedagogically and ethically relevant within the vocational education environment. Thus, AI holds significant potential in supporting the creation of a modern, efficient, and futureoriented learning process for the creative industry.